Beam penumbra reduction of Gamma Knife machine model 4C using Monte Carlo simulation. (May 2020) - Mahmoudi, Atefeh; Geraily, Ghazale; Hadisinia, Tahereh; Shirazi, Alireza; Najafzadeh, Milad
Highlights: Considerable reduction in physical penumbra was achieved using the designed filters. The most penumbra reduction was seen for lead filter of 4 mm collimator. The curved lateral surface of the filters led to lower hot spots near the beam edge. Lead filters caused lower hot spots and beam attenuation than to the tungsten filters. Negligible variations were seen by increasing SDD parameter. Abstract: Background and objective: In small radiation fields used in stereotactic radiosurgery penumbra is an important portion of the field size especially when critical organs at risk are located near the treatment sites. This study was aimed to reduce penumbra width (90%–50% isodose lines) of Gamma Knife (GK) machine by investigating of source to diaphragm distance (SDD) and designing compensating filter. Methods: Compensating filters at the end of the helmet collimators with the aim of reducing penumbra as well as reducing hot spots appeared near the edge of beam were modeled using Monte Carlo simulation code. Moreover, the SDD parameter was increased as one of the effective factors on penumbra width. Results: Results showed that single beam penumbra width using optimal design of filters was decreased by 59.49%, 42.50%, 39.02% and 34.44% with attenuation of 30.53%, 13.67%, 11.43% and 9.82% for 4, 8, 14 and 18 mm field sizes, respectively. Conclusions: The designed filters lead to considerable reductions in single beams penumbra width as well as a noticeable reduction in maximum dose emerged near the beam edge due to the curved lateral surface of filters.